The role of angiotensin converting enzyme (insertion)/(deletion) and angiotensin II type 1 receptor (A1166C) gene polymorphisms in antiproteinuric effect of ACE inhibitors in type 2 diabetic Iraqi patients - Ansam Abdulameer Yahya, Dheyaa Jabbar Kadhim, Nassar Abdalaema Abdalhadi (Journal of Applied Pharmaceutical Science, 2024)
The angiotensin converting enzyme (ACE) I\D gene polymorphism influences the blood ACE enzyme activity. Renoprotective effect of ACE inhibitors (ACEIs) varies among patients due to genetic variation, particularly in Renin-Angiotensin-Aldosterone System genes. This study investigates the genetic variations of ACE I\D and AGT1RA1166C gene polymorphisms in the antiproteinuric effect of ACEI therapy in type 2 diabetes mellitus (T2DM) patients. This is a cross-sectional study that included 76 T2DM patients who are ACEI users, divided into two groups: T2DM without diabetic kidney disease (DKD) included 31 patients, and T2DM with DKD included 45 patients. Urine samples were taken for measurement of urine albumin and creatinine, then calculation of albumin-creatinine ratio (ACR). Blood samples were taken for the measurement of serum parameters and also for the extraction of DNA for genetic evaluation of ACEI/D and AGT1RA1166C gene polymorphisms. The results reveal that T2DM patients carrying the ID genotype have significantly lower ACE1 levels compared to DD and II carriers (p = 0.012). When grouping patients according to the ACR, serum ACE1 and angiotensin-converting enzyme 2 (ACE2) levels were higher in DKD compared to normalbuminuric patients, with the only significant difference for ACE2. After subdividing according to ACE I\D genotypes, the ACE2 differences were only significant in DD genotype carriers (p = 0.049) between DKD and normalbuminuric groups. While for AGT1RA1166C polymorphisms, the AC genotype shows non-significantly lower levels for ACE1 and ACE2. After subdividing according to AGT1RA1166C genotypes, ACE2 levels were significantly higher in DKD patients carrying the AA genotype (p = 0.015). Binary logistic regression analysis revealed that both ACE (I\D) and AGT1RA1166C genes are significant predictors of ACE1 levels after controlling age, gender, and DKD state. This study concluded that both genes are predictors of ACE1 levels; in addition, ID genotype carriers and AC genotype carriers had lower ACE1 and ACE2 levels with lower ACR and higher glomerular filtration rate, identifying better ACEIs responses in ID and AC carriers.
Keywords: Angiotensin converting enzyme1, angiotensin converting enzyme2, diabetic kidney disease, albumin: creatinine ratio, ACE I\D genotype, AGT1RA1166C genotype, angiotensin converting enzyme inhibitors